Leaf‐herbivore attack reduces carbon reserves and regrowth from the roots via jasmonate and auxin signaling. Issue 4 (5th August 2013) - Machado, Ricardo A. R.; Ferrieri, Abigail P.; Robert, Christelle A. M.; Glauser, Gaétan; Kallenbach, Mario; Baldwin, Ian T.; Erb, Matthias
Summary: Herbivore attack leads to resource conflicts between plant defensive strategies. Photoassimilates are required for defensive compounds and carbon storage below ground and may therefore be depleted or enriched in the roots of herbivore‐defoliated plants. The potential role of belowground tissues as mediators of induced tolerance–defense trade‐offs is unknown. We evaluated signaling and carbohydrate dynamics in the roots of Nicotiana attenuata following Manduca sexta attack. Experimental and natural genetic variability was exploited to link the observed metabolite patterns to plant tolerance and resistance. Leaf‐herbivore attack decreased sugar and starch concentrations in the roots and reduced regrowth from the rootstock and flower production in the glasshouse and the field. Leaf‐derived jasmonates were identified as major regulators of this root‐mediated resource‐based trade‐off: lower jasmonate levels were associated with decreased defense, increased carbohydrate levels and improved regrowth from the rootstock. Application and transport inhibition experiments, in combination with silencing of the sucrose non‐fermenting (SNF) ‐related kinase GAL83, indicated that auxins may act as additional signals that regulate regrowth patterns. In conclusion, our study shows that the ability to mobilize defenses has a hidden resource‐based cost below ground that constrains defoliation tolerance. Jasmonate‐ and auxin‐dependent mechanisms may lead to divergent defensive plant strategies against herbivores in nature.